Tutte Polynomial of Multi-Bridge Graphs - Julian A. Allagan (Computer Science Journal of Moldova, 2013)
In this paper, using a well-known recursion for computing the Tutte polynomial of any graph, we found explicit formulae for the Tutte polynomials of any multi-bridge graph and some $2-$tree graphs. Further, several recursive formulae for other graphs such as the fan and the wheel graphs are also discussed.